Construction of Internet +home Care Quality Supervision Indicators in China Based on the Delphi Method - Ma G; Hou J; Peng S; Liu Y; Shi Z; Fan Y; Zhang J (Dove Medical Press, 2022)
Guiyuan Ma,1 Jianmei Hou,1 Sha Peng,1 Yanhui Liu,1 Zhengkun Shi,1 Yuhua Fan,1 Jinghui Zhang1- 3 1Teaching and Research Section of Clinical Nursing, Xiangya Hospital of Central South University, Changsha, 410008, People's Republic of China; 2National Clinical Research Center for Geriatric Disorders, Xiangya Hospital of Central South University, Changsha, 410008, People's Republic of China; 3Mobile Health-Ministry of Education Laboratory, Changsha, 410008, People's Republic of ChinaCorrespondence: Jinghui Zhang, Teaching and Research Section of Clinical Nursing, Xiangya Hospital of Central South University, No. 87 Xiangya Road, Kaifu District, Changsha, People's Republic of China, 410008, Tel +86 15874032339, Email zhangjh-1206@163.comBackground: With the aging of China's population, the incidence rate of chronic diseases is rising. At the same time, residents' health awareness is also increasing. Implementing Internet +home care is an inevitable trend in adapting social development. Currently, Internet +home care is in the pilot stage in China, relevant institutional measures are neither standardized nor perfect, and there is no set of quality supervision indicators (QSIs).Purpose: The construction of Internet +home care QSIs in China will provide a theoretical basis for Internet +home care quality supervision.Materials and Methods: The Service-Quality model was used as the theoretical framework, and a literature review, semi-structured interviews, focus group discussions, and Delphi consultations determined the contents of the QSIs and the weight of each indicator.Results: Internet +home care QSIs were constructed and included 5 first-level indicators, 17 secondary indicators, and 69 tertiary indicators. The effective recovery rates of the two rounds of Delphi expert consultation were 100% and 85%, the expert authority coefficients were 0.810 and 0.833, and the Kendall harmony coefficients were 0.189 and 0.125 (P< 0.01). The final set of Internet +home care QSIs was as follows: tangibility (4 secondary and 16 tertiary indicators), reliability (4 secondary and 19 tertiary indicators), guarantee (5 secondary and 20 tertiary indicators), responsiveness (2 secondary and 8 tertiary indicators), and empathy (2 secondary and 6 tertiary indicators).Conclusion: The construction of Internet +home care QSIs based on the SERVQUAL model is scientifically valid, and the indicators are reliable. They provide guidance and reference values for the continuous improvement and promotion of Internet +home care. This work also provides a theoretical basis for researching and developing an Internet +home care quality supervision platform.Keywords: SERVQUAL model, Internet +home care, delphi survey, quality supervision indicator